2024
DOI: 10.1002/pi.6601
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric approaches to organic polymeric materials

Mark Rigel R Ali,
Szeemaine D Tigno,
Eugene B Caldona

Abstract: Piezoelectricity refers to the ability of certain materials to generate electric charges when subjected to mechanical stress or strain, and vice versa. This phenomenon has been widely studied in inorganic materials, such as quartz and ceramics, and has found numerous applications in sensing, actuation, and energy harvesting. There has been a growing interest in piezoelectricity for polymeric materials that are lightweight, flexible, and highly processable for a wide range of applications, including sensors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 127 publications
(244 reference statements)
0
1
0
Order By: Relevance
“…The chemical composition of a surface also primarily influences its surface energy. ,, For instance, Zisman et al demonstrated that the surface energy decreases with increasing fluorine content in a polymer, following the sequence: CH 2 > CH 3 > CF 2 > CF 3 . , Fluoropolymers exemplify this principle such that the presence of highly polarized and inert C–F bonds promotes material stability and offers a multifaceted defense mechanism against environmental degradation. This attribute renders them invaluable for designing insulating layers that promote ionic permeability and prevent electron transfer between the metal and corrosive medium, thereby averting the oxidation process. Polyvinylidene fluoride (PVDF) and its CF 3 -containing copolymer, PVDF- co -hexafluoropropylene (PVDF–HFP), represent two exemplary fluoropolymers extensively employed in the coating manufacturing industry. Renowned for their exceptional inertness, these polymers offer remarkable corrosion and wear resistance, alongside mechanical integrity, film-forming characteristics, low surface energy, and thermal stability. , The synergy between PVDF’s durability and chemical resistance and HFP’s inclusion promoting ease of processability yields coatings that boast mechanical flexibility, outstanding protective properties, and lower surface energy. , Despite their inherently low surface energy, these fluoropolymers alone cannot achieve superhydrophobicity. , Customizing rough surfaces using materials with low surface energy or generating a rough surface on hydrophobic materials is typically employed to achieve superhydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of a surface also primarily influences its surface energy. ,, For instance, Zisman et al demonstrated that the surface energy decreases with increasing fluorine content in a polymer, following the sequence: CH 2 > CH 3 > CF 2 > CF 3 . , Fluoropolymers exemplify this principle such that the presence of highly polarized and inert C–F bonds promotes material stability and offers a multifaceted defense mechanism against environmental degradation. This attribute renders them invaluable for designing insulating layers that promote ionic permeability and prevent electron transfer between the metal and corrosive medium, thereby averting the oxidation process. Polyvinylidene fluoride (PVDF) and its CF 3 -containing copolymer, PVDF- co -hexafluoropropylene (PVDF–HFP), represent two exemplary fluoropolymers extensively employed in the coating manufacturing industry. Renowned for their exceptional inertness, these polymers offer remarkable corrosion and wear resistance, alongside mechanical integrity, film-forming characteristics, low surface energy, and thermal stability. , The synergy between PVDF’s durability and chemical resistance and HFP’s inclusion promoting ease of processability yields coatings that boast mechanical flexibility, outstanding protective properties, and lower surface energy. , Despite their inherently low surface energy, these fluoropolymers alone cannot achieve superhydrophobicity. , Customizing rough surfaces using materials with low surface energy or generating a rough surface on hydrophobic materials is typically employed to achieve superhydrophobicity.…”
Section: Introductionmentioning
confidence: 99%